2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24114
|View full text |Cite
|
Sign up to set email alerts
|

First-year Engineering Courses' Effect on Retention and Workplace Performance

Abstract: Due to a drop in the number of students enrolling and persisting in engineering programs, there is currently a lack of qualified engineering graduates, which jeopardizes both the health of the U.S. economy and the security of the nation. This issue has led to the development and implementation of a variety of pre-engineering and first-year engineering experiences designed to recruit more students to engineering and to retain them once they have chosen to pursue a degree in engineering. At the University of Cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…If structured properly, certain first-year engineering courses can have a significant positive impact on first-year retention [53]. Makerspaces present an opportunity to transform countless engineering programs by providing an educational means of student engagement via hands-on projects and further development of a large range of fundamental engineering skills that are currently being underdeveloped [54].…”
Section: The Makerspace Course: Engineering Methods Tools and Practicmentioning
confidence: 99%
See 1 more Smart Citation
“…If structured properly, certain first-year engineering courses can have a significant positive impact on first-year retention [53]. Makerspaces present an opportunity to transform countless engineering programs by providing an educational means of student engagement via hands-on projects and further development of a large range of fundamental engineering skills that are currently being underdeveloped [54].…”
Section: The Makerspace Course: Engineering Methods Tools and Practicmentioning
confidence: 99%
“…Dougherty [66] declares that the term "maker" is universal and essential to human identity, "describing each one of us, no matter how we live our lives or what our goals might be". A common reason students pursue engineering is because they enjoy the process of creation and the ability to work with their hands [53], and such practices are certainly prevalent throughout ENGR 111. The structure of ENGR 111 provides a context and potential for addressing motivational barriers in a manner that traditional classroom testing cannot do.…”
Section: The Makerspace Course: Engineering Methods Tools and Practicmentioning
confidence: 99%
“…Some have suggested that strategies to improve retention in the first year include hands-on engineering projects 10,11 and real-world experience 12 . Participation in co-ops increases self-efficacy which is reported to improve retention; albeit co-op experiences do not usually occur until after the first year 8 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…These course are becoming prevalent at many engineering programs and vary widely in implementation. Common approaches include providing students with hands-on experiences 8 , introducing students to industry professionals 10 , and focusing on under-performing demographics 5 .…”
Section: Introductionmentioning
confidence: 99%